ANALYSIS OF FACTORS AFFECTING QUALITY FROM ROAD CONSTRUCTION PROJECTS WEST SUMATRA PROVINCE - Gultom, Rahmi Fitriana; Carlo, Nasfrizal; BQS, Wahyudi P Utama (Fakultas Teknik Universitas Muhammadiyah Sumatera Barat, 2024)
In connection with road is supporter main in the development, then quality from road the must become something convenience is important user road. However at in fact Lots found quality results work a path that doesn't in accordance with what is required, so happen consequential damages age plan should not yet happened. Objective study that is For identify factors and analyze the most influential factor to quality project development road West Sumatra Province as well measure connection influencing factors to quality project. Method research used that is method study in a manner quantitative that is with spread questionnaire to para respondent. Results research conducted there are 5 influencing factors quality from project development road West Sumatra Province namely factor implementation occupation, factor power work, factor individual, factors equipment, factors method work